2002
DOI: 10.1097/00042737-200203000-00017
|View full text |Cite
|
Sign up to set email alerts
|

IgA-class transglutaminase antibodies in evaluating the efficacy of gluten-free diet in coeliac disease

Abstract: A substantial number of coeliac patients with negative tissue transglutaminase or endomysial antibodies may still have manifest mucosal villous atrophy. Small bowel biopsy is therefore still necessary to ensure that the gluten-free diet is adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
2
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 19 publications
5
81
2
9
Order By: Relevance
“…On the other hand, serological markers have relatively low negative predictive value in predicting mucosal damage in patients on a gluten-free diet. In a follow-up biopsy study of 87 adult patients, 27 showed villous atrophy (Marsh type 3 lesion, see later) despite the fact, that anti-tissue transglutaminase antibodies (tTG-Ab) were negative in 16 (59%) [27]. Thus, the significance of persistent histological changes in the patients on a gluten-free diet is currently not entirely clear.…”
Section: Treated Celiac Disease and Follow-up Biopsiesmentioning
confidence: 99%
“…On the other hand, serological markers have relatively low negative predictive value in predicting mucosal damage in patients on a gluten-free diet. In a follow-up biopsy study of 87 adult patients, 27 showed villous atrophy (Marsh type 3 lesion, see later) despite the fact, that anti-tissue transglutaminase antibodies (tTG-Ab) were negative in 16 (59%) [27]. Thus, the significance of persistent histological changes in the patients on a gluten-free diet is currently not entirely clear.…”
Section: Treated Celiac Disease and Follow-up Biopsiesmentioning
confidence: 99%
“…40,97,100 For example, in a series of 57 consecutive patients, 53% had normalized tTG IgA, but three out of five of these had ongoing villous atrophy. Conversely, one-third of the patients who still had raised tTG antibody levels at 12 months had normal histology.…”
Section: Coeliac Serology Normalization Of Coeliac Antibodiesmentioning
confidence: 99%
“…Despite clinical improvement on the GFD, villous atrophy may persist. 40,97,118,119 Symptom assessment cannot be advocated as a reliable method for determining absence of persistent small bowel villous atrophy.…”
mentioning
confidence: 99%
“…However, these tests are insufficiently sensitive to reflect occasional dietary transgressions (Kaukinen et al 2002, Tursi et al 2006. The degree and duration of gluten exposure will affect the results.…”
Section: Utility Of Serological Testing In Follow-upmentioning
confidence: 99%